Ovarian Metastasis from Colorectal Adenocarcinoma - Fillmann, Lúcio Sarubbi; Fillmann, Henrique Sarubbi; Fillmann, Laura Pinho; Tubiana, Ana Paula Reginatto; Ribeiro, Raquel; Coelho, Mariana (Journal of Coloproctology, 2021)
Introduction Ovarian metastases of gastrointestinal origin, also called Krukenberg tumors, have a guarded prognosis. Physicians need to look for alternatives in diagnosis and treatment for this clinical condition in order to improve the outcome of the patients.Objectives To report the experience of the authors in the treatment of these patients, and to perform a review of the literature on the epidemiology, clinical presentation, diagnosis, treatment, and prognosis for ovarian metastases from colorectal cancer.Methods We collected clinical information regarding the patients treated for ovarian metastasis from colorectal adenocarcinoma at our coloproctology service, and performed a search on the PubMed database using the terms colorectal cancer, ovarian metastasis, Krukenberg tumor and surgery.Conclusion Large abdominal tumors are the most frequent presentation of ovarian metastasis from colorectal cancer. The diagnosis is based on a histopathological analysis, levels of carcinoembryonic antigen (CEA) and cancer antigen 125 (CA-125), and immunohistochemical studies for the cytokeratin 20 (CK20), caudal-type homeobox 2 (CDX2) and vilina markers. Citoreductive surgical procedures are the most promising approach to treatment, with the highest impact on overall survival. The prognosis is negatively influenced by the extent of the metastasis, by citoreductive surgical procedures with persistence of macro- or microscopic foci of the disease, and by low scores on the general well-being index of the patient.
Keywords: colorectal cancer; ovarian metastasis; surgery